Autoimmune pancreatitis - role of intestinal microbiota in pathogenesis. Review of the literature - Wiejak, Katarzyna; Schok, Katarzyna; Jasek, Jakub (Journal of Education, Health and Sport, 2024)
Introduction: Autoimmune pancreatitis is a type of chronic autoimmune inflammation that can be divided into two types. Type 1 is a clinical manifestation of IgG4-mediated disease, while type 2 may coexist with inflammatory bowel diseases. Objective: The aim of the study is to review the literature on the role of the intestinal microbiota in the pathogenesis of autoimmune pancreatitis. Methods: A literature review was conducted on databases such as PubMed and Google Scholar using the terms: ”autoimmune pancreatits”, “intestinal dysbiosis”, “intestinal microbiome”, and “pathogenesis”. Conclusions: The intestinal microbiota has an impact on the development of autoimmune pancreatitis, but it is not the main pathogenic factor, but rather a risk factor.